2019
DOI: 10.1016/j.mex.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Landfill site selection using a hybrid system of AHP-Fuzzy in GIS environment: A case study in Shiraz city, Iran

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 38 publications
(24 reference statements)
0
29
0
Order By: Relevance
“…Ever increasing population growth in cities in pace with economic growth has led to an increased production of various types of municipal solid waste, in particular, medical waste [1]. Proper management of municipal waste in order to reduce its adverse effects on the environment and the health of citizens is a necessity [2][3][4]. Different types of municipal solid waste have numerous effects on health, environmental, economic and social aspects; Nowadays, the littered waste management is considered in priority [5].…”
Section: Introductionmentioning
confidence: 99%
“…Ever increasing population growth in cities in pace with economic growth has led to an increased production of various types of municipal solid waste, in particular, medical waste [1]. Proper management of municipal waste in order to reduce its adverse effects on the environment and the health of citizens is a necessity [2][3][4]. Different types of municipal solid waste have numerous effects on health, environmental, economic and social aspects; Nowadays, the littered waste management is considered in priority [5].…”
Section: Introductionmentioning
confidence: 99%
“…To minimize the bad odor generated from a landfill site that affects near residents, it is important to consider wind direction. 62 Northwest is the prevailing wind direction in the study area; therefore, this direction is unsuitable to locate a sanitary landfill. SRTM DEM was used to obtain prevailing wind types in the study area.…”
Section: Methodsmentioning
confidence: 99%
“…There are many studies on the site selection of SWSL by integrating multi-criteria decision-making methods with GIS The study of Küçükönder and Karabulut (2007) has been revealed that multi-criteria analysis method and GIS can produce an effective and applicable results by considering many physical, environmental, social and economic factors in the site. Similarly Karimi et al (2019), Pasalari et al (2019) and Ali et al (2021) indicate that an integrating approach of GIS and multi-criteria decision analysis is effective in landfill site selection. Khorsandi et al (2019) used AHP and order of preference technique according to similarity to ideal solution (TOPSIS) models to weight the layers and prioritize the determined areas, respectively.…”
Section: Introductionmentioning
confidence: 95%